Explaining the corporate demand for risk management: financial and economic views - Ashby, Simon (1998)
The purpose of this thesis is to review a number of academic perspectives on the practice of risk management in primarily widely-held (i.e. quoted) firms. In particular the currently dominant modern finance approach is criticised on the grounds that it offers an overly narrow view of corporate risk management behaviour. The core of the modern finance approach is that risk management is said to exist as a means to alleviate the adverse impact of various financial and capital market based agency and transactions costs that prevent the firm's stakeholders from achieving a Pareto efficient distribution of risk amongst themselves. However, in what follows it is argued that the presence of such agency or transactions costs do not provide a complete rationale for corporate risk management. Indeed fruitful research is already being done in the areas of organisational behaviour, sociology and psychology. Yet, what remains to be fully explored is the short run economic impact of risk management on a firm. In view of this a new economic framework for risk management is proposed based on the twin economic concepts of risk related "pure penalties" (which represent an unambiguous cost to a firm) and "technological nonlinearities" (which can affect the structure of a fine's revenue, cost and production functions). Both of these phenomena can have a significant effect on the expected profits of a firm. Moreover, it is demonstrated that there are numerous scenarios in which risk management may be used by an expected profit maximising firm.